Signs in Kawen Sai Ceremony of Tetun Tribe - Adrianus Berek (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This study examines the meaning of signs in Kawen Sai, the traditional patrilineal marriage system of Tetun tribes of Belu Regency. Qualitative descriptive method was applied in designing the study. In addition, Pierce’s theory of semiotics was used as the underlying parameter in analyzing the data. Observation, interview and recording techniques were used in collecting the data from 10 informants. The results show that signs in Kawen Sai ceremony comprise 36 forms and belong to symbol. Meaning implied beyond these signs are sanctity, ritual, modesty, majesty, respect, petition, hope, social, and communication systems.